1977
DOI: 10.1007/bf00438297
|View full text |Cite
|
Sign up to set email alerts
|

The scientific foundations of clinical enzymology

Abstract: Clinical enzymology is the study of the activity and properties of enzymes in specimens (usually of blood) taken from patients, as an aid to the diagnosis and understanding of disease. Research in many areas of enzymology is undertaken to strengthen the foundations on which the clinical interpretation of such enzyme measurements rests. Some aspects of this research are briefly described.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1978
1978
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…A marked decrease was encountered in total urinary ALP activity obtained for normal controls (0.34 ± 0.2 U/mmol creatinine) compared with the results obtained by [2] who showed that ALP for adults was 1.6 U/mmol creatinine [23] .…”
Section: Kidney Patientsmentioning
confidence: 39%
“…A marked decrease was encountered in total urinary ALP activity obtained for normal controls (0.34 ± 0.2 U/mmol creatinine) compared with the results obtained by [2] who showed that ALP for adults was 1.6 U/mmol creatinine [23] .…”
Section: Kidney Patientsmentioning
confidence: 39%
“…Lipid profile, CK-MB, CBC, LFT are pathologically diagnosed by the therapeutic process [41][42][43][44][45][46][47][48][49]. 1)…”
Section: Biochemical Parameters Evaluationmentioning
confidence: 99%